DEVELOPMENT OF THE “SI MENTAL BK” APPLICATION AS A MEDIUM FOR EXPRESSING STUDENTS' MENTAL HEALTH AT THE UPT SPF SMP NEGERI 9 MAKASSAR - Febriana Angraeni; Abdullah Pandang; Sahril Buchori (Jurnal Konseling Pendidikan Islam, 2026)
This study aims to develop the "SI MENTAL BK" application as a medium for disclosing student mental health at UPT SPF SMP Negeri 9 Makassar. The background of this research is based on the challenges in mental health services in Indonesia, where access to mental health services is still limited and many students are unaware of their mental health conditions. The method used in this research is Research and Development (R&D) with an approach that includes needs analysis, planning, product development, expert validation, and field testing. The results show that this application is highly needed by students and guidance counselors, with an average development needs score of 3.76 (very much needed category). The application’s validity is rated very good with an average score of 3.93, and its practicality also received positive evaluations with an average score of 3.93. The "SI MENTAL BK" application is expected to facilitate guidance counselors in identifying and addressing students' mental health issues effectively and efficiently, as well as providing relevant information for follow-up actions. This research makes a significant contribution to the development of technology-based guidance and counseling services in schools.